Career Preparation Traning Sebagai Upaya Peningkatkan Daya Saing Menghadapi Persaingan Dunia Kerja - Helmy, Irfan (LP3M Universitas Putra Bangsa, 2022)
Competition for university graduates in the world labour is increasing. The number of jobs offered is not proportional to the applicants or job applicants. This is indicated by the high number of unemployed in D3 and S1 graduates. One of the causes is the lack of preparation of students in facing the work before they graduate from college. Therefore, this service has the theme of career preparation training which aims to equip prospective alumni with skills and competencies, both practical and soft skills as an additional supplement in facing the competition in the real world of work. This training is carried out in one day with several materials, namely, training on making CVs, training on making application letters and training using job seekers applications such as jobstreet. Through this training package, students are expected to be able to prepare themselves early in the face of job competition